Prevalence of somatic symptoms amongst undergraduate medical students of Marathwada region of Maharashtra, India - Husain, Shaikh Arshiya Kaiser; Magare, Anwaya R.; Giri, Purushottam A.; Jadhav, Vijaykumar S. (International Journal Of Community Medicine And Public Health, 2020)
Background: The aim of medical education is to produce competent, physically and mentally strong health professionals, as they are going to be the pillars of the future health care system. Stress is one of the most common and process-oriented obstacles in medical education. It often exerts a negative effect on the academic performance, physical health, and psychological well-being of the students. Dealing with overloaded medical curriculum, competing with peers, being away from home and meeting high expectations imposed by parents and society to excel is among the common stressful transitions at this stage. Methods: A cross-sectional descriptive study was carried out amongst 352 undergraduate medical students of a private medical college in a rural area of Maharashtra during April to October 2019. The structured questionnaire was used to record the data. Collected data was used to assess the severity of mental health issues among medical students. Results: Majority 194 (55.11%) students were in the age of 18 to 20 years followed by 141 (40.06%) were in 21 to 23 years. There were 196 (55.68%) girl students and 156 (44.32%) boys. According to the various categories, 80 (22.73%) of the students had low stress scores, followed by 76 (21.59%) in minimal. A highly significant difference in stress scores was seen between boys and girls, which was more in boys. Conclusions: Study concluded that undergraduate medical students perceive minimal to very high stress presented as various systems that vary with the year of study and gender wise too. There is a further need to look into the various causes of stress.